N-acetyl-L-cysteine attenuated the toxicity of ZIF-8 on EA.hy926 endothelial cells by wnt/β-catenin pathway. (April 2023) - Tang, Yaxin; Jin, Lifang; Qi, Wenwen; Gao, Yue; Xie, Yixia; Xie, Xueying; Lv, Jianan; Jiang, Zhikai; Jiang, He; Fan, Caixia; Yan, Junyan
Abstract: As kinds of porous crystalline compounds, zeolitic imidazolate frameworks (ZIFs) have been developed quickly and attracted considerable attention for use in nano drug delivery systems, which raised concerns about cardiovascular disorders. At the present, the cytotoxic mechanism of ZIFs in cardiovascular disorders was still unclear. Our experiment explored the toxicity of ZIF-8, a typical kind of ZIFs, on human EA.hy926 vascular endothelial cells. The cell viability, ROS formation, apoptosis level, inflammatory response level, wound healing ability and atherosclerosis-related indicators of EA.hy926 endothelial cells were analyzed after ZIF-8 treatment. Meanwhile, we evaluated the ability of antioxidant N-Acetyl-L-cysteine (NAC) to attenuate the toxicity of ZIF-8 on EA.hy926 endothelial cells. As results, NAC attenuated ROS formation, cell apoptosis, LDH formation and endothelial dysfunction caused by ZIF-8. As the Wnt/β-catenin pathway was involved in endothelial cell dysfunction, we also studied the expression level of β-catenin and LEF1 in ZIF-8 and/or NAC treated EA.hy926 cells. As expected, ZIF-8 increased the protein expressions of β-catenin and LEF1in the IC50 group, which was significantly inhibited by co-treatment with NAC. Taken together, this study could help improve our understanding about the mechanism of ZIF-8-induced endothelial cells injury and NAC had therapeutic potential in preventing ZIF-8-associated endothelial dysfunction by wnt/β-catenin pathway. Graphical abstract: Unlabelled Image Highlights: The toxicity of ZIF-8 on human EA.hy926 vascular endothelial cells. NAC attenuated toxicity and endothelial dysfunction caused by ZIF-8. NAC had therapeutic potential in preventing ZIF-8-associated endothelial dysfunction by wnt/β-catenin pathway.